Increased protein oxidation and decreased expression of nuclear factor E2‐related factor 2 protein in skin tissue of patients with diabetes. (31st December 2014) - Lee, Y. J.; Kwon, S. B.; An, J. M.; Kim, C. H.; Lee, S. H.; Choi, C. Y.; Nam, D. H.; Park, J. W.; Nam, H. S.; Lee, S. H.; Lee, M. W.; Cho, M. K.
Summary Background Reactive oxygen species (ROS) contribute to the cell dysfunction and tissue damage that result from glucolipotoxicity in diabetes. ROS formation in cells causes oxidative stress, thereby activating oxidative damage‐inducing genes. Nuclear factor erythroid 2‐related factor 2 (Nrf2) has been shown to play an essential role in the vital defence mechanisms that help cells cope with oxidative stress. Aim To compare Nrf2 protein expression in nondiabetic skin tissue with that in diabetic skin tissue. Methods Nrf2 expression was evaluated by Western blotting, reverse transcription (RT)‐PCR, and immunohistochemical staining in diabetic and nondiabetic skin tissues. Dinitrophenylhydrazone derivatives of protein carbonyls in the oxidized proteins were measured by oxyblotting analysis. Cytoplasmic and nuclear Nrf2 protein expression was determined to identify the activity and level of Nrf2. Results Protein oxidation, a marker of oxidative stress, was found to be increased in diabetic skin tissue. In subcellular fraction analysis, Nrf2 protein was detected in the nuclei and cytoplasm of nondiabetic skin tissues, and the Nrf2 protein band was identified from among the multiple bands detected, using small interfering RNA‐mediated Nrf2 gene silencing. Compared with nondiabetic tissue, diabetic skin tissue showed simultaneous downregulation of Nrf2 at both the mRNA and protein levels. Nuclear condensation, loss of nuclei, and vacuolization were seen in some parts of the specimen by haematoxylin and eosin staining of diabetic skin tissue. Immunohistochemical staining of Nrf2 confirmed the RT‐PCR and Western blotting results. Conclusions Collectively, our data show that expression of Nrf2 is clearly downregulated in diabetic skin tissue, and suggest that Nrf2 may be necessary for protection against glucose‐induced oxidative stress.